Sham elections amid the war in Myanmar: Prospects for national stability and international cooperation - Felix Heiduk (Stiftung Wissenschaft und Politik (SWP), 2026)
Five years after the bloody military coup and amid a civil war, elections have taken place in Myanmar. They were neither free nor fair, nor was any attempt made to keep up an appearance of even minimum democratic standards. From the outset, the main purpose of the elections was not political participation but an authoritarian-led transition from military rule to a "civilian" government. The country's new executive is intended to appear legitimate both nationally and internationally (on account of the ballot) and at the same time consolidate the military's dominance. For its part, Myanmar's military leadership claims the elections mark a "new beginning" to restore political stability in the country and break its international isolation. The reference here is, among others, to the European Union (EU) and its member states, which have imposed sanctions against Myanmar. However, they should not believe the myth of a "civilian" elected government and a "return" to constitutional order; and, accordingly, they should not seek to normalise relations with Myanmar for the time being.
Keywords: 320; Myanmar; international isolation; "polycrisis"; China; EU; UN; ASEAN; Rohingya; National Unity Government (NUG); military coup; civil war; elections; ethnic armed organisations (EAOs); authoritarian-led transition; National League for Democracy (NLD); Aung San Suu Kyi